1996
DOI: 10.1161/01.atv.16.2.208
|View full text |Cite
|
Sign up to set email alerts
|

Importance of a Novel Oxidative Mechanism for Elimination of Intracellular Cholesterol in Humans

Abstract: We have recently demonstrated that cultured human alveolar macrophages efficiently convert cholesterol into excretable 27-oxygenated products. We show here that increasing the intracellular concentration of cholesterol by a factor of 10 leads to about a twofold increase in the excretion of 27-oxygenated products from cultured macrophages. Inhibition of the sterol 27-hydroxylase caused a significant intracellular accumulation of cholesterol. A direct comparison was made between flux of cholesterol and 27-oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
117
0
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(130 citation statements)
references
References 19 publications
9
117
0
1
Order By: Relevance
“…45 Interestingly, the 27-hydroxylase pathway has been suggested to be important in the removal of extrahepatic cholesterol. 46 As the accumulation of cholesterol preceded that of 27HC, the formation of the latter may be interpreted as a physiological (potentially anti-atherogenic) response to cholesterol load.…”
Section: Discussionmentioning
confidence: 99%
“…45 Interestingly, the 27-hydroxylase pathway has been suggested to be important in the removal of extrahepatic cholesterol. 46 As the accumulation of cholesterol preceded that of 27HC, the formation of the latter may be interpreted as a physiological (potentially anti-atherogenic) response to cholesterol load.…”
Section: Discussionmentioning
confidence: 99%
“…This oxidative mechanism has the potential to eliminate up to about half of the content of cholesterol in the cultured cells in 24 h. Both the alcohol and the acid are primary products of the sterol 27-hydroxylase, and 3␤-hydroxy-5-cholestenoic acid is thus formed by three consecutive hydroxylations at the same methyl group (2). We have also demonstrated that there is a continuous net flux of 27-oxygenated products to the liver, where these metabolites are efficiently converted into bile acids (3). It was shown that up to 4% of the total formation of bile acids in humans may occur by a mechanism involving extrahepatic 27-hydroxylation of cholesterol (3).…”
mentioning
confidence: 83%
“…We have also demonstrated that there is a continuous net flux of 27-oxygenated products to the liver, where these metabolites are efficiently converted into bile acids (3). It was shown that up to 4% of the total formation of bile acids in humans may occur by a mechanism involving extrahepatic 27-hydroxylation of cholesterol (3).…”
mentioning
confidence: 83%
“…In the CID spectrum of [16,16,17(or 20) ] isotopomer and glycine conjugate, and also 3␤,7␣-dihydroxychol-5-en-24-oic acid, were oxidized with cholesterol oxidase, reacted with GP hydrazine, and analyzed by ES mass spectrometry. Oxidation of these bile acids with cholesterol oxidase results in conversion of the 3␤-hydroxyl group to a ketone, and movement of the ⌬ 5(6) double-bond to ⌬ 4 (5) . In this translocation one of the deuterium atoms on C-4 of the deuterated isotopomers is lost to give a mass increase overall of 4 Da (i.e., [ In the low mass range of the spectrum, the usual pattern of fragment ions at m/z 80.05, 94.07, 108.08, 109.08, 120.05/120.08 and 137.07 is distorted by the presence of ions at m/z 81.07 and 99.08.…”
Section: Group (Iii) Fragment Ions: Gp Hydrazone Neutral-loss Fragmenmentioning
confidence: 99%
“…However, other oxysterols are intermediates in the formation of steroid hormones. Oxysterol formation can occur in many tissues and organs, and conversion of an oxysterol to a bile acid is not restricted to the liver [3][4][5][6][7]. Hormonally active steroids can also be synthesized from cholesterol outside the endocrine organs.…”
mentioning
confidence: 99%